Ekspertyza dokumentu „Skills Development and Employability in Europe: The New Skills Agenda” - Przyszczypkowski, Kazimierz; Cytlak, Izabela; Jarmużek, Joanna; Pawłowski, Roman; Szafran, Joanna (Wydawnictwo Naukowe UAM, 2017)
This article is a critical analysis of the "Skills Development and Employability in Europe: The New Skills Agenda" document. The purpose of the discussion is to analyze the 10 problem areas identified and formulated in the document, paying particular attention to the perception and implementation of these issues from the perspective of European countries. The recommendations presented for each of the issues may provide important guidance for developing a vision of vocational education targeting the labor market of the European Union.
"Skills Development and Employability in Europe: The New Skills Agenda” – document expertise
Keywords: educational policy; employment; European Union; education and labor market; New Skills Agenda